The limits of ‘professionalisation from above’: On the ‘re-professionalisation’ of street-level policing in England - Bacon, Clifford (Criminology & criminal justice, 2025)
The occupation of policing is in crisis. Criticism of police failings has created intense pressure for the traditional ‘occupational closure’ model of policing as a craft to be replaced by new ‘professional’ models associated with ‘evidence-based policing’, harm reduction, risk management and vulnerability. Various change initiatives have amounted to the ‘re-professionalisation’ of policing, whereby previous models of police professionalism based on craft, discretion and judgement have been abandoned and replaced by new protocols, guidelines and enhanced external scrutiny. This article explores how these changes are interpreted by operational police officers, using qualitative interviews and ethnographic fieldwork to explore officers’ application and understanding of the new requirements. Whereas some literature argues that ‘police culture’ remains largely unchanged, our data illustrate how officers’ daily routines are in a state of enforced flux. While there was some limited support for the rationale for change, officers were highly critical of the practical implementation of policing vulnerability, were sceptical of the new doctrine of ‘professionalism’, and resentful of new managerial controls and priorities. This does not amount to the stubborn persistence of a ‘reform-proof’ police culture. Rather, officers described substantial change to the everyday culture and practice of policing, in ways they regard as confused, self-defeating and unworkable. We argue that professionalisation imposed ‘from above’ via dogmatic managerial logic can have detrimental implications for occupations and the public they serve.